(untitled) (American Journal of Islam and Society, 2006)
Books Reviewed: Sachiko Murata, Chinese Gleams of Sufi Light: Wang Taiyu’s “Great Learning of the Pure and Real” and Liu Chih’s “Displaying the Concealment of the Real Realm.”Albany: SUNY Press, 2000; Maria Jaschok and Shui Jingjun, The History of Women’s Mosques in Chinese Islam: A Mosque of Their Own. Richmond, UK: Curzon Press, 2000; Jean A. Berlie, Islam in China: Hui and Uyghurs between Modernization and Sinicization. Bangkok: White Lotus, 2004; Sheila Hollihan-Elliot, Muslims in China. Philadelphia: Mason Crest Publishers, 2006. With a population conservatively estimated at 20 million (and, according to some sources, as high as 50 million), the Muslims of China remain one of the least studied and most misunderstood Muslim communities in the world. After decades of relative neglect, however, over the past few years several books have been published that seek to shed light on different aspects of the historic, religious, and contemporary lives of China’s Muslims. This review essay will survey four recent works written by a wide range of scholars. Research on Islam in China has been hindered by many factors, including the difficulty of gaining expertise in both Chinese studies and Islamic studies, learning both modern and classical Chinese and Arabic, the longstanding prejudices of Han Chinese scholars regarding the country’s minority peoples, together with the similarly long-standing prejudices of many western scholars regarding Islam. The earliest major work on the Muslim communities of China was published in 1910, by Marshall Broomhall of the China Inland Mission. Titled Islam in China: A Neglected Problem, its main purpose was to educate Christian missionaries in China about the location, customs, and history of the indigenous Muslims in order to facilitate proselytization activities among them ...